Yapısal uyum programlarının Türkiye sanayine ve sanayi politikalarına etkisi - Şentürk, Çoşkun (My University, 2010)
YAPISAL UYUM PROGRAMLARININ TÜRKİYE SANAYİNE VE SANAYİ POLİTİKALARINA ETKİSİ Çoşkun ŞENTÜRK Bu çalışma ile uluslararası kurumların (özellikle IMF ve DB) yapısal uyum programları aracılığı ile Türkiye sanayileşmesine ve sanayi politikalarına olan etkisi irdelenmeye çalışılmıştır. Kuruldukları günden itibaren tüm dünyada, gelişmekte olan ülkelerin kalkınma/ sanayileşme süreçlerinde daima etkili olan uluslararası kurumlar, Türkiye’de de 1980 sonrasında, ekonomide yaşanan dönüşümle birlikte varlıklarını ve etkinliklerini fazlası ile arttırmıştır. Çalışma, azgelişmişlik, kalkınma ve sanayileşme ilişkilerinin incelenmesi ve yapısal uyum programlarının açıklanmasının ardından, Türkiye’nin yaşadığı sanayileşme sürecini irdeleyerek, bu süreci sanayi politikası araçları ile değerlendirmeyi ve yapısal uyum politikalarının Türkiye sanayisi üzerindeki etkilerini göstermeyi amaçlamıştır. Sanayi, Kalkınma, Yapısal Uyum

THE EFFECTS OF STRUCTURAL ADJUSTMENT PROGRAMMES ON TURKEY’S INDUSTRY AND INDUSTRIAL POLICIES This study has intended to examine the effects of the structural adjustment programmes implemented by international organizations (IMF and the World Bank in particular) on Turkey’s industrialization and industry policies. Since their inception, the international organizations have always exerted powerful influence on developing countries’ development and industrialization processes all over the world and similarly these organizations have increased their presence, and activities in Turkey considerably following the transformation the country’s economy underwent after 1980. The study has aimed to examine the relationship among underdevelopment, development, and industrialization and following the explanation of structural adjustment programmes, to scrutinize the industrialization process Turkey has gone through by evaluating this process using industry policy instruments and to demonstrate the effects of structural adjustment policies on Turkey’s industry. Industry, Development, Structural Adjustment Programmes, Turkey
Keywords: Sanayi Politikaları; Sanayi_Türkiye